THE IMPACT OF THE FINANCIAL CRISIS ON LONG MEMORY: EVIDENCE FROM EUROPEAN BANKING INDICES - Pece Andreea Maria; Mihut Ioana Sorina; Oros Olivera Ecaterina (Annals of the University of Oradea: Economic Science, 2014)
We have analyzed the impact of the financial crisis on the existence of the long term dependency for European banking indices. By estimating Hurst Exponent, ARFIMA and FIGARCH models we found that major financial crisis such as, Mexican, Asian and Russian, Argentine crisis and Global crisis from 2008-2009 had different effects on long memory. In the case of STOXX 600 Bank Index, when estimating an ARFIMA models by using Willinger, Taqqu and Teverovsky method, the H-estimate was higher than 0.5, highlighting the presence of long memory during Mexican and Global financial crisis from 2008-2009. In the case of MSCI Europe Bank Index we found evidence of long memory during Asian and Russian crisis and Argentine crisis. For both indices, during the Global crisis, the results of FIGARCH models reflected the presence of long term dependency in volatility with covariance non-stationary, but mean reverting, showing the likelihood of persistence of a shock for a long period. Moreover, during Argentine crisis, the results reflected evidence of stationarity intermediate memory process.